INVESTIGATION OF THE PREVALENCE OF FOREIGN BODY EXPOSURE TO THE EYES AND THE USE OF PROTECTIVE EQUIPMENT IN THE EMPLOYEES OF THE ÇALI INDUSTRIAL ZONE - Yusuf Duru; Derya Doğanay; Nagihan Amuk Hamidi; Levent Özdemir; Hafize Gökben Ulutaş (International Journal of Health Services Research and Policy)
This study aims to determine the prevalence of foreign bodies in the eyes of people working in the Bursa Çalı Industrial Zone. A survey was conducted to evaluate ocular foreign body exposures in workers working in Çalı Industrial Zone. The demographic characteristics of the participants, presence of foreign body exposure to the eye, use of protective goggles, and medical leave of absence were questioned. A total of 400 participants, 351 male (87.8%) and 49 females (12.2%), were included in the study. The mean age of the participants was 36.92±10.27 years, and the average working time in the sector was 8.87±8.06 years. Of the 400 participants included in the study, 153 (38.3%) had a history of ocular foreign body exposure. While the most frequently exposed foreign body was metal burrs (83.7%), the most exposed workers were welders (85.5%). Those who reported that they constantly used protective goggles at work were 42.1%, and those who used them occasionally were 48.7%. Ocular foreign body exposure rates detected in that industrial zone were relatively high. Although the use of protective goggles is high, ocular injuries still suggest that personal protective equipment and its use should be more effective. Any eye trauma that is prevented will reduce suffering, hospital admission, loss of workforce/labor, and the burden on the health system and the economy.